Effects of Pranayama on Human Memory Improvement (International Journal of Physiology, 2020)
Aim and Objective: The purpose of this study is to evaluate results of memory scores in normal healthy adult.Brain areas involved in memory such as the hippocampus, the amygdala, the striatum, or the mammillarybodies are thought to be involved in specific types of memory. Pranayama is to control the body function bycontrolling our breathMaterials and Method: This study was conducted in the yoga center on 62 subjects. Subjects were trainedfor breath holding yoga training. they performed for total of 30 minutes duration daily. At the end of fourweek the subjects were examined by WECHSLER memory scale.Observations: The results showed increase in scores of all types of test DSF, DSB, and all are highlysignificant P